Preparation and characterization of a number of complexes of Mn (II), Co (II), Ni (II), Cu (II), Hg (II) ions With a mixture of saccharin ligands, barbituric acid and thiobarbituric (Journal of the College of Basic Education, 2022)
This thesis includes, preparation and diagnosis of new twenty-one complex Of ions Mn (II) , Co (II) , Ni (II) , Cu (II) , Hg (II)With a mixture of saccharin legends and Barbituric / Thiobarbituric acid.The work included interaction of elements ions above With a mixture of saccharin legends and Barbituric / Thiobarbituric acid with Mole fraction (1: 1: 1) (Metal : saccharin : Barbituric or Thiobarbituric acid ) complexes were Diagnosed that have been prepared by fusion degrees , the magnetic sensitivity , careful analysis of the elements (CHNS) , molar Electrical conductivity techniques and and infrared spectrum , electronic spectrum and Nuclear Magnetic Resonance spectrum of the proton (H.NMR) techniques .and Through the results that were obtained chemical formulas were suggested for the first part complexes were as follows: -]M(BA) (sac)(H2O) 4 [ Cl] M(TBA) (sac)(H2O)4 [ ClWhereasMn (II) , Co (II) , Ni (II) , Cu (II) M=BA = Barbituric acid.TBA = Thiobarbituric acid .sac= Saccharine .And it had a octahedral geometric shape Where Saccharine was linked to the central metal by nitrogen atom And Barbituric acid was linked to the central metal by oxygen atom.And Thiobarbituric acid was linked to the central metal by sulfur atom.And complexes Hg (II) have chemical formulasCl[Hg(BA)(sac)]Cl [Hg(TBA)(sac)]With linear geometric structure.Where Saccharine was linked to the central metal by nitrogen atom And Barbituric acid was linked to the central metal by oxygen atom.And Thiobarbituric acid was linked to the central metal by sulfur atom.